V+N MISCOLLOCATIONS IN THE WRITTEN PRODUCTION OF UNIVERSITY LEVEL STUDENTS - Zinkgräf, Magdalena (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract The study of collocation – the restricted way in which two or more words combine across texts – has recently gained much relevance. The acquisition of these combinations has proved an important obstacle for non-native speakers of a foreign language as evinced in recorded unusual combinations of words. This paper analyses nonstandard collocations present in the written production of Spanish-speaking university students of English as a foreign language (EFL), in search of recurrent patterns and strategies that may explain these inappropriate collocations as a way to contribute to EFL teaching and learning. The results show a considerable influence of learners’ mother tongue, which induces them to translate literally from L1 into L2 one or both elements in any given collocation. Semantic overlap between appropriate forms and possible synonyms of either the base or the collocate appears to be another factor leading to error. The study also points to some verbs which in this particular context might require consistent and explicit teaching. Resumen El estudio de la colocación – la combinación restringida de dos o más palabras en diversos textos – ha cobrado mucha relevancia en las últimas décadas. La adquisición de estas combinaciones se convierte en un obstáculo importante para hablantes no-nativos de un idioma extranjero, quienes combinan palabras de manera poco usual. Este trabajo analiza las desviaciones colocacionales registradas en la producción escrita de alumnos universitarios de inglés como lengua extranjera cuya lengua materna es el español para explorar estructuras recurrentes y las estrategias que las generan, y contribuir, de esta manera, a la enseñanza y el aprendizaje del inglés como lengua extranjera. Los resultados señalan la importante influencia de la lengua materna, que impulsa a estos alumnos a traducir, en forma directa, uno o ambos elementos en las combinaciones del español al inglés. Otro factor que conduce a errores es la superposición semántica entre la base o el colocado en una colocación y posibles sinónimos. El estudio indica también la necesidad de una instrucción explícita y sistemática de ciertos verbos en este contexto educativo en particular.